Carbon‐equivalent metrics for albedo changes in land management contexts: relevance of the time dimension. Issue 6 (2nd September 2016) - Bright, Ryan M.; Bogren, Wiley; Bernier, Pierre; Astrup, Rasmus
Abstract: Surface albedo is an important physical property by which the land surface regulates climate. A wide and growing body of literature suggests that failing to account for surface albedo can result in suboptimal or even counterproductive climate‐motivated policies of the land‐based sectors. As such, albedo changes are increasingly included in climate impact assessments of forestry and other land sector projects through conversion of radiative forcings into carbon or carbon dioxide equivalents. However, the prevailing methodology does not sufficiently accommodate dynamic albedo changes on land or CO2 in the atmosphere. We present two new metrics designed to address these deficiencies, referring to them as the time‐dependent emissions equivalent and the time‐independent emissions equivalent of albedo changes. We demonstrate their application in various land management contexts and discuss their merits and uncertainties.